Análise do efeito da terapia combinada com estimulação magnética transcraniana repetitiva (EMtr) e gameterapia sobre a capacidade funcional motora e cognitiva de indivíduos portadores de DP - Costa, Maíra Lopes da (2019)
Parkinson's disease (PD) is a progressive disease that affects more than 1% of the world's population over 60 years old, making it the second most prevalent degenerative disease in the world. There is an evident decline in functional capacity due to the motor and cognitive impairment typical of PD, triggering impairments in the basic and instrumental activities of daily living (ADLs) and consequently compromising the affected individuals’ quality of life, requiring alternative therapies that act concomitantly with the drug therapy. Thus, this study aimed to analyze the effect of combined therapy with Repetitive Transcranial Magnetic Stimulation (rTMS) and Exergaming on the motor and cognitive functional capacity of individuals with PD in the city of Campina Grande - PB. The study was longitudinal, experimental, double-blind, randomized, descriptive and analytical, with quantitative approach. The sample consisted of 20 individuals with PD, assisted by the Unified Health System (SUS). The research procedures were: Stage I - Recruitment of the sample and initial evaluation of the individuals, the following evaluation instruments were applied: Sociodemographic / clinical evaluation form; Scale of Disability Stages of Hoehn and Yahr - EIHY; Unified Parkinson's Disease Assessment Scale - UPDRS; and Scales for Outcomes in Parkinson's Disease-Cognition (SCOPA-COG); Parkinson Disease Questionnarie-39 (PDQ-39); Baropodometer and Stabilometry. Step II - Allocation of individuals in the research groups: group active rTMS; group active rTMS and Exergaming; Group placebo rTMS and Exergaming; group placebo rTMS. The sessions were performed in the period of 2 weeks, 3 times a week, totaling the number of 6 sessions per group; Stage III - after the end of the intervention period, the re-evaluation of the experimental groups was performed. The same instruments from the pre-intervention period were applied, which were also applied to the individuals in the control group. The results were analyzed using the GraphPad Prism Statistics statistical software version 6.0. Data were expressed as mean, standard deviation of the mean, median, 25% and 75% percentile or percentage. The level of significance was set at p. <0.05. Regarding the ethical aspects, this work was submitted to the Research Ethics Committee of the Federal University of Paraíba. A total of 20 individuals with a mean age of 62.4 ± 10.18 years participated in the study, which did not present a change in disease staging during the study. There was significant improvement for the motivational / initiative items (p = 0.04), language (p = 0.008), falls (p = 0.04), gait (p = 0.006), motor symptoms (p = 0.009) intervention group, and between the group that underwent combination therapy with active rTMS and the placebo group. Significant improvements were observed in the executive function (p = 0.01), visuospatial function (0.02), and emotional aspect (p = 0.01) between active and placebo groups. It is possible to conclude that the combination therapy of rTMS and exergaming did not alter the staging of PD, the instrument UPDRS presented improvements for motivation, ADLs (specifically language, falls and gait), for motor alterations: speech articulation, fast movements and alternating hands and agility of the legs, cognition improved in attention domains, executive functions and visuospatial functions, the individuals' quality of life was improved in the emotional aspects, mobility and body discomfort, balance by increasing the pace of the step of the left foot.